Measuring race and ethnicity - Davis, Larry E.; Engel, Rafael J. (Springer eBook., 2011)
Racial and ethnic issues stand at the core of social, political, and economic concerns in an increasingly diverse America. Accordingly, how individuals from the various ethnic groups regard themselvesâ??and othersâ??is a salient focus of research studies across the disciplines. Measuring Race and Ethnicity gathers psychological measures of common phenomena such as racial identity, acculturation, and intra- and intergroup relations enabling researchers to compare concepts across groups and better evaluate differences and disparities. Most of the instruments date from the 1990s and later, while a number of still-useful earlier scales are included. Taken together, these tools strengthen a wide evidence base, and point to areas where new scales are warranted. Included in this volume: -Fourteen measures for African Americans, such as the Rejection Sensitivity Race Questionnaire and the Cultural Mistrust Inventory -Nine Caucasian-specific instruments, including the Race and Politics Survey and the Being White in America Scale -Nineteen acculturation scales for Latinos, some specific to Puerto Ricans, Cubans, and Chicanos -Eight Asian/Pacific Islander measures, including the Race-Related Stressor Scale and the Intergenerational Congruence in Immigrant Families Scale. -The Native American Acculturation Scale -Twenty-two generic measures, including the Experience of Discrimination Scale and the Scale of Ethnocultural Empathy Researchers in psychology, social work, and public health examining cultural and race-related topics will find an immediately relevant source of valid and reliable scales in Measuring Race and Ethnicity